Effect of Cathodic and Anodic Treatments of Carbon on the Electrode Kinetics of VIV/VV Oxidation-Reduction. Issue 8 (1st January 2015) - Bourke, A.; Miller, M. A.; Lynch, R. P.; Wainright, J. S.; Savinell, R. F.; Buckley, D. N.
Abstract : Cyclic voltammetry and electrochemical impedance spectroscopy were used to examine several types of carbon electrodes in V IV /V V in H2 SO4 . The materials investigated included glassy carbon, graphite, carbon paper, reticulated vitreous carbon and carbon fibers. In all cases the electrode kinetics of the V IV /V V oxidation-reduction reactions are enhanced by cathodic treatment of the electrode and inhibited by anodic treatment. Pronounced activation typically occurs at potentials more negative than +0.1 V (vs. Hg/Hg2 SO4 ); the effect begins to saturate at about –0.6 V. Pronounced deactivation typically occurs at potentials more positive than +0.7 V. Both activation and deactivation occur rapidly during the first ∼10 s at the most negative and most positive potentials, respectively. The activation effect saturates quickly at the most negative potentials but the deactivation effect does not saturate on the time scales investigated. There is a considerable shift (∼1.1 V) between the potentials for activation and deactivation. Activated electrodes showed no significant loss of activity after standing in the electrolyte for 3 weeks; deactivated electrodes regained about 50% of their activity. The activation and deactivation effects were observed regardless of whether vanadium was present in the electrolyte and are attributed to oxygen-containing functional groups on the electrode surface.